Associations between neuropsychiatric and health status outcomes in individuals with probable mTBI. (February 2019) - Bomyea, Jessica; Flashman, Laura A.; Zafonte, Ross; Andaluz, Norberto; Coimbra, Raul; George, Mark S.; Grant, Gerald A.; Marx, Christine E.; McAllister, Thomas W.; Shutter, Lori; Lang, Ariel J.; Stein, Murray B.
Highlights: Health status outcomes were compared between those with mTBI, mTBI and PTSD, and controls in the INTRuST consortium. Neuropsychiatric predictors of health status outcomes were explored in those with mTBI. mTBI with PTSD demonstrated lowest health status, followed by mTBI only. Mental health symptoms, postconcussive symptoms, and some cognitive subtests were associated with health status. Abstract: Mild traumatic brain injury (mTBI) is a common occurrence, and may impact distal outcomes in a subgroup of individuals. Improved characterization of health outcomes and identification of factors associated with poor outcomes is needed to better understand the impact of mTBI, particularly in those with co-occurring posttraumatic stress disorder (PTSD). Participants in a data repository of the Injury and Traumatic Stress (INTRuST) Clinical Consortium ( n  = 625) completed functional disability [FD] and health-related quality of life [HRQOL] questionnaires, and a subset completed a neuropsychological assessment. FD and HRQOL were compared among participants with probable mTBI (mTBI), probable mTBI with PTSD (mTBI/PTSD), and health comparison participants (HC). Associations between symptoms, neuropsychological performance, and health outcomes were examined in those with probable mTBI with and without PTSD ( n  = 316). Individuals in the mTBI/PTSD group endorsed poorer health outcomes than those in the mTBI group, who endorsed poorer outcomes than those in the HC group. Individuals in either mTBI group performed worse than those in the HC on verbal learning and memory and psychomotor speed. Health outcomes were correlated with mental health and postconcussive symptoms, as well as neuropsychological variables. mTBI may adversely impact self-reported health, with the greatest effect observed in individuals with co-occurring mTBI/PTSD.